Mechanical and biological evaluation of two fresh pepper varieties - Zhang, Shanwen; Li, Shaowen; Dai, Min; Lu, Enhui; Liu, Sixing; Ge, Linquan; Zhang, Yongji; Guan, Chunsong; Xv, Binxing; Su, Wei; Miao, Hong (Frontiers in Plant Science, 2025)
The operation of roller-type pepper harvesters involves striking and pulling the peppers, which may result in incomplete detachment from their stems or cause surface damage or breakage of the peppers. The quality of the harvested peppers is directly influenced by the forces applied during striking and pulling. Therefore, the physical and mechanical properties of peppers are crucial for determining the structural and dynamic parameters of the screw rollers. This study selected Round peppers and the 'Bo 15' line pepper as experimental subjects. Growth parameters such as main stem diameter and fruit diameter were measured. And mechanical properties including tensile, bending, compressive, and shear strength were tested. Results showed that: two pepper varieties had a moisture content of 90% ± 1%. The main stem diameters of Round pepper and 'Bo 15' line pepper were 10.196 ± 1.508 mm and 13.44 ± 0.769 mm. The average diameter of round pepper was greater than that of 'Bo 15' line pepper. For mechanical stress, the 'Bo 15' line pepper exhibited stronger resistance, and the mechanical properties were as follows: tensile strength was 0.83 MPa, bending strength was 0.58 MPa, radial compressive strength was 0.25 MPa, and shear strength was 0.28 MPa. This study provides a basis for the design of low damage harvesting device for fresh peppers and the selection of varieties suitable for mechanical harvesting.